Plant Transcription Factors from the Homeodomain-Leucine Zipper Family I. Role in Development and Stress Responses. - Perotti, María Florencia; Ribone, Pamela Anahí; Chan, Raquel Lía (Wiley, 2017)
In front of stressful conditions plants display adaptation mechanisms leading to changes in their morphology, physiology, development and molecular composition. Transcription factors (TFs) play crucial roles in these complex adaptation processes. This work is focused in the homeodomain-leucine zipper I (HD-Zip I) family of TFs, unique to plants. First discovered in 1991, they were identified and isolated from monocotyledonous and dicotyledonous plants showing high structural similarity and diversified functions. These TFs have, besides the homeodomain and leucine zipper, conserved motifs in their carboxy-termini allowing the interaction with the basal machinery and with other regulatory proteins. The model dicotyledonous plant Arabidopsis thaliana has 17 HD-Zip I members; most of them regulated by external stimuli and hormones. These TFs are involved in key developmental processes like root and stem elongation, rosette leaves morphology determination, inflorescence stem branching, flowering and pollen hydration. Moreover, they are key players in responses to environmental stresses and illumination conditions. Several HD-Zip I encoding genes from different species were protected in patents because their overexpression or mutation generates improved agronomical phenotypes. Here we discuss many aspects about these TFs including structural features, biological functions and their utilization as biotechnological tools to improve crops.
https://openpolicyfinder.jisc.ac.uk/id/publication/3647?from=single_hit
Keywords: Fisiología vegetal; Factores de transcripción; Biotecnología; Transcription factors; Homeodomain-leucine zipper; HD-Zip I; Arabidopsis thaliana; Biotechnological tools